Investigation of the effect of oligo-xylulose on the intestinal flora under pressure overload in mice based on 16S rRNA gene sequencing: Oligo-xylulose effects via 16S rRNA sequencing - Long, Jianfeng; Qi, Xiaoke; Tang, Zhenjie; Zhou, Kang (Cellular and Molecular Biology, 2024)
The relationship between gut microbiota dysbiosis and heart failure has been drawing increasing attention. This study aimed to investigate the effects of oligo-xylulose (XOS) on the gut microbiota of mice with heart failure induced by pressure overload. A chronic heart failure mouse model was constructed by pressure overload, and XOS were administered in their diet. The gut microbiota was analyzed using 16S rRNA gene sequencing, and the effects of XOS on the microbiota composition were evaluated. . XOS supplementation improved the balance of intestinal microbiota in mice under pressure overload, increasing the abundance of beneficial bacteria, such as Bifidobacterium and Lactobacillus, while decreasing the abundance of harmful bacteria, such as Desulfovibrio and Enterococcus. XOS has potential as a dietary supplement to improve the balance of intestinal microbiota and benefit individuals with heart failure. The findings of this study suggest that modulating the gut microbiota could be a novel strategy for treating heart failure.